2017
DOI: 10.1080/15384047.2017.1323580
|View full text |Cite
|
Sign up to set email alerts
|

Current status of research and treatment for non-small cell lung cancer in never-smoking females

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide with over 1 million deaths each year. The overall prognosis of lung cancer patients remains unsatisfactory, with a 5-year overall survival rate of less than 15%. Although most lung cancers are a result of smoking, approximately 25% of lung cancer cases worldwide are not attributable to tobacco use. Notably, more than half of the lung cancer cases in women occur in non-smokers. Among non-small-cell lung cancer (NSCLC) cases, cigarette-smokers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 120 publications
3
53
1
2
Order By: Relevance
“…This result is supported by the fact that 73.2% of EGFR positive patients received TKI treatment in our study. Additionally, never-smoker lung cancer, especially of adenocarcinoma histology, was highly associated with female sex of East Asian ethnicity and higher prevalence of genomic alterations [36], which was in accordance with our findings. Our study demonstrated significant differences in survival curves amongst the four EGFR mutation sites, with a good prognosis in patients with E19 dels and relatively adverse prognosis in patients with an E21 mutation.…”
Section: Discussionsupporting
confidence: 91%
“…This result is supported by the fact that 73.2% of EGFR positive patients received TKI treatment in our study. Additionally, never-smoker lung cancer, especially of adenocarcinoma histology, was highly associated with female sex of East Asian ethnicity and higher prevalence of genomic alterations [36], which was in accordance with our findings. Our study demonstrated significant differences in survival curves amongst the four EGFR mutation sites, with a good prognosis in patients with E19 dels and relatively adverse prognosis in patients with an E21 mutation.…”
Section: Discussionsupporting
confidence: 91%
“…Among the 5 of 8 lung cancer cases in the validation cohort, the ANN could identify all (100%) of these patients who had pulmonary lesions and initially presented with GGNs <20 mm, which were nally con rmed as adenocarcinoma. In several studies performed in Asian cohorts, the majority of lung cancer patients were non-smokers with pulmonary adenocarcinoma spectrum lesions, which typically presented as pure GGNs or partially solid nodules [33,34]. The current literature shows that larger GGNs (variable cut-off, range 10.5~15.0 mm) tend to be more aggressive or appear as invasive pulmonary adenocarcinoma [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinase inhibitors are used in patients with EGFR mutations and ALK rearrangements. In addition, immunotherapy has also recently become a major therapeutic modality in nsclc [20][21][22] . Despite that progress, 5-year survival in lung adenocarcinoma is less than 12%-15% 23 .…”
Section: Discussionmentioning
confidence: 99%